The role of national spiritual heritage in the formation of haman capital (Journal of Philosophy Culture and Political Science, 2015)
The article analyzes the main aspects of the socio-cultural problems of modern higher education, in particular, the problem of forming a holistic world view among students in the eclectic world of pluralism and integration of IT. The article in Kazakhstani educational, cultural, social and spiritual problems in a context of "human capital" of the main aspects analyzed. The authors of the article in the world dreamed of innovative technologies for the formation of a single world view of young students that priority attention is given to the formation of human capital. Capitalization of human potential - a key factor in the importance of the information society. Sufficient investment in this sector has become a priority in any of the nation's economy. After all, the ultimate goal - people were financed more revenue than the original, is the ability of self-growth. The authors of the article, the value for the process of national philosophical heritage plays a key role in formulating.
Keywords: world view; higher education; human capital; innovative technologies; tehnologic cultural heritage; information society.